(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
Alkaloids, flavonoids, saponins, starch, tannins, terpenoids and Vitamin-C distributions in four medicinal plants from different places of Bangladesh were assessed. Fifteen samples of four medicinal plants were investigated namely Adhatodha vasica Nees, Andrographis peniculata (Burm. f.) Nees, Withania somnifera (Linn.) Dunal and Asparagus racemosus Willd. These plants are locally known as Basak, Kalomegh, Ashagandha and Sotomuli. Leave samples contain alkaloids, terpenoids, saponins, tannins, flavonoids and Vitamin-C except starch. In root samples alkaloids, flavonoids, saponins and Vitamin-C were present except tannins. Terpenoids were present in sotomuli root, but absent in ashagandha root. Starch was absent in sotomuli root but present in ashagandha root. All of the plants were collected from different districts of Bangladesh. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17330 Bangladesh J. Sci. Ind. Res. 48(3), 193-196, 2013